“I don't have Huntington's disease”: the boundaries between acceptance and understanding - Gustavo Leite Franklin; Hélio A. Ghizoni Teive; Francisco Eduardo Cardoso (Arquivos de Neuro-Psiquiatria)
Huntington's disease (HD) is an inherited disease that leads to an inexorable progression of motor, cognitive and psychiatric disturbances. In the initial stages, the symptoms are not clearly disabling, and the patient may present a lack of awareness about the symptoms themselves, which we call anosognosia. However, anosognosia might not justify all passivity of the HD patient in face of the diagnosis. Patients may also experience the denial of illness, as a stage of grief, expected to happen in the face of the diagnosis of any neurodegenerative disorder. In addition, people with HD tend to be more apathetic, and more silent, in regular consultations. In the present article, the authors express a point of view, discussing the behavior of the HD patient, in which there is a multifactorial passivity, in the face of the diagnosis and of the disease itself. Having the proper knowledge of this situation may prepare the neurologist to better understand the patient and the evolution of the disease.